Population-based Incidence and Etiology of Community-acquired Neonatal Viral Infections in Bangladesh: A Community-based and Hospital-based Surveillance Study. Issue 7 (July 2015) - Farzin, Azadeh; Saha, Samir K.; Baqui, Abdullah H.; Choi, Yoonjoung; Ahmed, Nawshad Uddin; Simoes, Eric A.F.; El Arifeen, Shams; Al-Emran, Hassan M.; Bari, Sanwarul; Rahman, Syed M.; Mannan, Ishtiaq; Crook, Derrick; et al.
Abstract : Background: The etiology of >90% of cases of suspected neonatal infection remains unknown. We conducted community-based surveillance in conjunction with hospital-based surveillance in a rural region in Bangladesh from June 2006 to September 2007 to assess the incidence and etiology of community-acquired viral infections among neonates. Methods: Community health workers (CHWs) assessed neonates at home on days 0, 2, 5 and 8 after birth and referred cases of suspected illness to the hospital (CHW surveillance). Among neonates with clinically suspected upper respiratory tract infection (URTI), pneumonia, sepsis and/or meningitis, virus identification studies were conducted on nasal wash, cerebrospinal fluid and/or blood specimens. In the hospital-based surveillance, similar screening was conducted among all neonates (referred by CHWs and self-referred) who were admitted to the hospital. Results: CHW surveillance found an incidence rate of 15.6 neonatal viral infections per 1000 live births with 30% of infections identified on the day of birth. Among neonates with suspected sepsis, a viral etiology was identified in 36% of cases, with enterovirus accounting for two-thirds of those infections. Respiratory syncytial virus was the most common etiologic agent among those with viral pneumonia (91%) and URTI (68%). There was a low incidence (1.2%) of influenza in this rural population. Conclusion: Viral infections are commonly associated with acute newborn illness, even in the early neonatal period. The estimated incidence was 5-fold greater than reported previously for bacterial infections. Low-cost preventive measures for neonatal viral infections are urgently needed. Abstract : Supplemental Digital Content is available in the text.